A-to-I miR-378a-3p editing can prevent melanoma progression via regulation of PARVA expression - Guermarie Velazquez-Torres; Einav Shoshan; Cristina Ivan; Li Huang; Enrique Fuentes-Mattei; Harrison Paret; Sun Jin Kim; Cristian Rodriguez-Aguayo; Victoria Xie; Denise Brooks; Steven J. M. Jones; A. Gordon Robertson; et al. (Nature Communications, 2018)
In melanoma, reduced ADAR1 impairs A-to-I microRNA editing. Here, the authors show that miR-378a-3p undergoes this editing in non-metastatic cells and the edited form of miR-378a-3p binds to the PARVA oncogene, inhibiting its expression and preventing melanoma progression and metastasis.